2014
DOI: 10.1007/s12094-014-1178-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-25 expression level is an independent prognostic factor in epithelial ovarian cancer

Abstract: The increased expression of miR-25 is closely related to poor prognosis of EOC, indicating that miR-25 may serve as a predictive biomarker for the prognosis of EOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 16 publications
1
24
1
Order By: Relevance
“…Therefore, it is critical to understand the roles of miRNAs in cancer development and progression, and explore their potential as novel therapeutic targets for the treatment of patients with cancer. Previous studies have implicated miR-25-3p in several types of human cancer (17)(18)(19); however, the roles of miR- 25-3p in OS have yet to be elucidated. The present study aimed to assess the expression of miR-25-3p in OS tissues and cell lines, and explore its biological functions in OS cells in vitro.…”
Section: Upregulation Of Microrna-25-3p Inhibits Proliferation Migramentioning
confidence: 99%
“…Therefore, it is critical to understand the roles of miRNAs in cancer development and progression, and explore their potential as novel therapeutic targets for the treatment of patients with cancer. Previous studies have implicated miR-25-3p in several types of human cancer (17)(18)(19); however, the roles of miR- 25-3p in OS have yet to be elucidated. The present study aimed to assess the expression of miR-25-3p in OS tissues and cell lines, and explore its biological functions in OS cells in vitro.…”
Section: Upregulation Of Microrna-25-3p Inhibits Proliferation Migramentioning
confidence: 99%
“…Specific miRNA expression and/or levels of expression in particular tissues may predict certain diseases. Thus, these miRNAs can be selected as candidate biomarkers for the diagnosis and prognosis of various tumours [20,22,24]. The expression and function of various miRNAs have been reported in glioma [17,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al found that miR-25 promoted migration and invasion of esophageal squamous cell carcinoma cells [16]. In OC, Wang et al reported that miR-25 was increased in OC, and elevated expression of miR-25 was associated with poor prognosis of EOC [11]. Zhang et al also found that miR-25 promoted OC cell proliferation by targeting B cell lymphoma 2-interacting mediator of cell death (Bim) [17].…”
Section: Discussionmentioning
confidence: 99%
“…In OC, miRNAs act as either oncogenes or tumor suppressor [9,10]. MiR-25 has been found to be increased in OC; however, its detailed role remains unclear [11].…”
Section: Introductionmentioning
confidence: 99%